2017
DOI: 10.3389/fcimb.2017.00121
|View full text |Cite
|
Sign up to set email alerts
|

Shiga Toxin Subtypes of Non-O157 Escherichia coli Serogroups Isolated from Cattle Feces

Abstract: Shiga toxin producing Escherichia coli (STEC) are important foodborne pathogens responsible for human illnesses. Cattle are a major reservoir that harbor the organism in the hindgut and shed in the feces. Shiga toxins (Stx) are the primary virulence factors associated with STEC illnesses. The two antigenically distinct Stx types, Stx1 and Stx2, encoded by stx1 and stx2 genes, share approximately 56% amino acid sequence identity. Genetic variants exist within Stx1 and Stx2 based on differences in amino acid com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 43 publications
4
15
0
Order By: Relevance
“…The vt2 subtypes a , c and/or d were identified in 98.6% of vt2 positive isolates – subtypes which have been associated with the development of haemorrhagic colitis or HUS ( Orth et al, 2007 ; Kawano et al, 2008 ), as well as increased toxin potency in vitro and in vivo ( Fuller et al, 2011 ). High levels of these subtypes in bovine isolates have been previously reported in Australia ( Brett et al, 2003 ) and the US ( Shridhar et al, 2017 ), and may represent a pool of transmissible virulence factors that could increase the pathogenicity of strains that acquire them. Additional studies should also be conducted to determine whether toxin-negative strain populations of the VTEC serotypes identified in this study co-exist with their toxin-positive counterparts; these could represent a reservoir of potential human pathogens, or alternatively could indicate that certain sub-populations are not likely to be associated with human disease.…”
Section: Discussionmentioning
confidence: 88%
“…The vt2 subtypes a , c and/or d were identified in 98.6% of vt2 positive isolates – subtypes which have been associated with the development of haemorrhagic colitis or HUS ( Orth et al, 2007 ; Kawano et al, 2008 ), as well as increased toxin potency in vitro and in vivo ( Fuller et al, 2011 ). High levels of these subtypes in bovine isolates have been previously reported in Australia ( Brett et al, 2003 ) and the US ( Shridhar et al, 2017 ), and may represent a pool of transmissible virulence factors that could increase the pathogenicity of strains that acquire them. Additional studies should also be conducted to determine whether toxin-negative strain populations of the VTEC serotypes identified in this study co-exist with their toxin-positive counterparts; these could represent a reservoir of potential human pathogens, or alternatively could indicate that certain sub-populations are not likely to be associated with human disease.…”
Section: Discussionmentioning
confidence: 88%
“…Strains may express one or both families of the toxins, and several variants of each are known (Melton-Celsa, 2014;EFSA BIOHAZ Panel et al, 2020). Ruminants may preferentially harbor different stx variants (Mora et al, 2012;Bai et al, 2016;Shridhar et al, 2017). The subtypes stx 2d and stx 1c-are strongly associated with sheep, whereas recent reports have highlighted the increasing prevalence of subtype stx 2O118 in ovine ruminants (Koch et al, 2001;Ramachandran et al, 2001;Brett et al, 2003;Alonso et al, 2016).…”
Section: Stec Pathogenic Factorsmentioning
confidence: 99%
“…Because Shiga toxin genes are located on a prophage, it is suggested that the serogroups lacking these genes either have lost the prophage or have the potential to acquire the prophage (Bielaszewska et al, 2007 ). A majority of the non-O157 top-six STEC have been show to carry Shiga toxin 1 gene (Shridhar et al, 2017 ). There is evidence that the type of stx gene carried by STEC in cattle is dependent on the age of the animal and season.…”
Section: Discussionmentioning
confidence: 99%